Backup Expression of the PhaP2 Phasin Compensates for phaP1 Deletion in Herbaspirillum seropedicae, Maintaining Fitness and PHB Accumulation - Alves, Luis P. S.; Teixeira, Cícero S.; Tirapelle, Evandro F.; Donatti, Lucélia; Tadra-Sfeir, Michelle Z.; Steffens, Maria B. R.; de Souza, Emanuel M.; de Oliveira Pedrosa, Fabio; Chubatsu, Leda S.; Müller-Santos, Marcelo (Frontiers in Microbiology, 2016)
Phasins are important proteins controlling PHB granules formation, their number into the cell and stability. The genome sequencing of the endophytic and diazotrophic bacterium Herbaspirillum seropedicae SmR1 revealed two homologous phasin genes. To verify the role of the phasins on PHB accumulation in the parental strain H. seropedicae SmR1, isogenic strains defective in the expression of phaP1, phaP2 or both genes were obtained by gene deletion and characterized in this work. Despite of the high sequence similarity between PhaP1 and PhaP2, PhaP1 is the major phasin in H. seropedicae, since its deletion reduced PHB accumulation by ≈ 50 % in comparison to the parental and ΔphaP2. Upon deletion of phaP1, the expression of phaP2 was 6-fold enhanced in the ΔphaP1 strain. The responsive backup expression of phaP2 partially rescued the ΔphaP1 mutant, maintaining about 50% of the parental PHB level. The double mutant ΔphaP1.2 did not accumulate PHB in any growth stage and showed a severe reduction of growth when glucose was the carbon source, a clear demonstration of negative impact in the fitness. The co-occurrence of phaP1 and phaP2 homologous in bacteria relatives of H. seropedicae, including other endophytes, indicates that the mechanism of phasin compensation by phaP2 expression may be operating in other organisms, showing that PHB metabolism is a key factor to adaptation and efficiency of endophytic bacteria.